Jessica Pierce. Run, Spot, Run: The Ethics of Keeping Pets. Chicago: University of Chicago Press, 2016. - Kountaki, Dimitra (Conatus - Journal of Philosophy, 2019)
In her book Run, Spot, Run: The Ethics of Keeping Pets, bioethicist Jessica Pierce attempts to explore a narrower field of Animal Ethics, the ethics of keeping pets, as the title indicates. Τhere has not been much research in this field, although contemporary literature has dealt with certain issues within its context, such as the issue of euthanasia (Pierce’s previous book, The Last Walk, is dealing with this issue). The author states that her main aim is to lead the reader, by the time he reaches the last page of the book, to no longer be sure if the very practice of keeping pets is moral. Although the author proposes the use of a kinder language for discussing about pet keeping, she uses the accepted language throughout her book.